2012
DOI: 10.18433/j3d60r
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for Involvement of P-Glycoprotein in Brain Uptake of the Centrally Acting Analgesic, Tramadol in the Rat

Abstract: -Purpose. Tramadol Hydrochloride is a widely-used centrally acting analgesic drug, which has some features of being a P-gp substrate. The present study evaluates the functional involvement of Pgp in CNS distribution of tramadol. Methods. The possibe involvement of P-glycoprotein in brain distribution of tramadol was evaluated using a pharmacokinetic approach in two groups of Pgp-inhibited and control rats. Six male Sprague-Dawley rats were used in each group to collect plasma and brain at 1, 5, 10, and 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Tramadol accumulation could also have resulted from changes in gastrointestinal absorption due to increase in solubility/permeability and/or active efflux transporter inhibition. Both of these are questionable as tramadol is considered to have high intestinal solubility and permeability (class I of the Biopharmaceutics Classification System) (Lassoued et al, 2011) and the role of P-glycoproteins in the transport of tramadol across cell mem-branes remains unresolved (Slanar et al, 2007;Sheikholeslami et al, 2012). The transient analgesia observed in horses with pain due to chronic laminitis (Guedes et al, 2012) was likely due to reasons other than decreased or inconsistent bioavailability (Giorgi et al, 2007;Shilo et al, 2008;Stewart et al, 2011) as a context-sensitive cumulative effect was detected in this study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Tramadol accumulation could also have resulted from changes in gastrointestinal absorption due to increase in solubility/permeability and/or active efflux transporter inhibition. Both of these are questionable as tramadol is considered to have high intestinal solubility and permeability (class I of the Biopharmaceutics Classification System) (Lassoued et al, 2011) and the role of P-glycoproteins in the transport of tramadol across cell mem-branes remains unresolved (Slanar et al, 2007;Sheikholeslami et al, 2012). The transient analgesia observed in horses with pain due to chronic laminitis (Guedes et al, 2012) was likely due to reasons other than decreased or inconsistent bioavailability (Giorgi et al, 2007;Shilo et al, 2008;Stewart et al, 2011) as a context-sensitive cumulative effect was detected in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Tramadol accumulation could also have resulted from changes in gastrointestinal absorption due to increase in solubility/permeability and/or active efflux transporter inhibition. Both of these are questionable as tramadol is considered to have high intestinal solubility and permeability (class I of the Biopharmaceutics Classification System) (Lassoued et al ., ) and the role of P‐glycoproteins in the transport of tramadol across cell membranes remains unresolved (Slanar et al ., ; Sheikholeslami et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In situ rat brain perfusion studies by Cisternino et al, showed that tramadol likely shared the same hypothetical proton-coupled antiporter as nicotine and diphenhydramine at the BBB (20). Another rat study found that Pgp inhibition through verapamil pre-treatment had no effect on the brain concentration of tramadol, suggesting it is not a likely P-gp substrate (172).…”
Section: Tramadolmentioning
confidence: 99%
“…In addition, neither tramadol nor its active metabolite Odesmethyltramadol appear to be P-gp substrates, potentially avoiding transporter-mediated interactions with a number of anti-cancer molecules (172,175) …”
Section: Potential Implications For Cancer Therapymentioning
confidence: 99%
“…However, in humans, no loss-of-function mutations have been described [82]. It has not been established if tramadol is a substrate of P-gp, an in vitro study and one in vivo study in rat have suggested that it is not [87,88]. However, venlafaxine, being structurally very similar to tramadol [89], is a P-gp substrate in mice [90].…”
Section: Abcb1mentioning
confidence: 99%